Microcrystalline-Silicon-Oxide-Based N-Type Reflector Structure in Micromorph Tandem Solar Cells. (8th April 2012) - Li, Chiung-Nan; Fang, Hsuan-Yin; Chen, Yu-Hung; Yeh, Chun-Ming; Huang, Chian-Fu; Wang, Yu-Chih; Hung, Kai-Hsiang; Pan, Yen-Yu; Wu, Chien-Liang; Chen, Yu-Ru; Liu, Jun-Chin; Chen, Chun-Heng
Abstract : N-type microcrystalline silicon oxide thin films (n-μ c-SiO x :H) have been deposited by VHF-PECVD (40 MHz) with reactant gas mixtures of CO 2 /SiH 4 and H 2 . N-μ c-SiO x thin films exhibiting low refractive index value (n 600 nm 2 ), and medium/high conductivity (≧ 10 - 9 S/cm) are suitable to be used as an " n-type reflector " in micromorph tandem solar cells. Transmission electron microscopy (TEM) results show that microstructures of n-μ c-SiO x :H thin films contain nanocrystalline Si particles, which are randomly embedded in the a-SiO x matrix. This specific microstructure provides n-μ c-SiO x :H thin films excellent optoelectronic properties; therefore, n-μ c-SiO x :H thin films are appropriate candidates for " n-type reflector " structures in Si tandem solar cells.